Penguatan Produksi Dan Pemasaran Melalui Platform Media Sosial pada Usaha Sale Pisang JA3R di Desa Pudak - Nurhayani; Tan, Syamsurijal; Haryadi; Rosmeli; Musnaini; Ekasari, Novita (Jurnal Pengabdian Tri Bhakti, 2025)
The JA3R banana sale business is one of the businesses located in RT 01 Pudak Village, Kumpeh Ulu District, Muaro Jambi Regency, Jambi Province. Although the banana sale business has been established for a long time, in its marketing it does not yet have a Google Business account to facilitate marketing with a wide reach and as a medium for customers to search for relevant products or services. On the other hand, the JA3R banana sale business in the production process, the drying stage is a key stage that determines the quality and durability of the product. The purpose of this community service is to increase production by using a digital marketing platform and focusing on the revitalization of the greenhouse as a place for drying bananas. The community service was carried out on August 28, 2025. The community service ran smoothly, partners worked together and actively during the community service implementation so that the goals that had been set were achieved. Business partners are now not only found by local customers through IG and Google Business, but have also succeeded in expanding their market reach outside the region. The key innovation in the form of implementing a greenhouse as a drying tool has overcome the fundamental problem of dependence on the weather, while ensuring product quality, consistency, and hygiene.